Analysis of Influences of ICT on Structural Changes in Japanese Commerce, Business Services and Office Supplies, and Personal Services Sectors Using Multivariate Analysis: 1985–2005 - Zuhdi, Ubaidillah; Mori, Shunsuke; Kamegai, Kazuhisa (The Asian Journal of Technology Management (AJTM), 2013)
This study analyzes influences of Information and Communication Technology (ICT) in the structural changes of Japanese industrial sectors from 1985 through 2005. ICT is represented by two explanatory variables, computers (including main parts and accessories) and telecommunications equipment. We investigate influences by the Constrained Multivariate Regression (CMR) model and test the statistical significance of this model by the Likelihood Ratio Test (LRT) method. We then perform microscopic analysis, focusing on the commerce, business services and office supplies, and personal services sectors. The results show that these variables, separately and jointly, had significant influence on structural changes in Japanese industrial sectors, including the analyzed ones. The patterns of influence in analyzed sectors are, however, different. Based on this difference, we can say that during 1985–2005 the business circumstances of the analyzed sectors were dissimilar.Keywords: ICT, Industrial Structural Changes, CMR, LRT, Japandoi:10.12695/ajtm.2013.6.2.5 How to cite this article:Zuhdi, U., Mori, S., and Kamegai, K. (2013). Analysis of Influences of ICT on Structural Changes in Japanese Commerce, Business Services and Office Supplies, and Personal Services Sectors Using Multivariate Analysis: 1985–2005. The Asian Journal of Technology Management 6 (2): 102-111. Print ISSN: 1978-6956; Online ISSN: 2089-791X. doi:10.12695/ajtm.2013.6.2.5